ANALISIS SEKTOR UNGGULAN DALAM MENUNJANG PEMBANGUNAN EKONOMI DI KOTA PAREPARE - Syukri, Fitriyani; Zakariah, Junaidin; Aminuddin, Aminuddin; Alamsyah, Alamsyah (Universitas Muhammadiyah Parepare, 2021)
This academic research was carefully conducted to typically know the accurate classification of the leading sectors in the Kota Parepare. The data typically used in common is secondary data which is taken directly from the Central Statistics Agency of the Kota Parepare. The data typically used are the empirical PDRB data of the City of Parepare from 2011-2019. This academic research was typically started from March to April 2020. Exploratory data analysis typically used Klassen Typology Analysis and Location Qoutien analysis. The direct results of this academic study typically indicate that: the leading sectors in the Kota Parepare in common are the water supply sector, waste processing, waste and recycling, the transportation and warehousing sector, the financial services sector, and insurance and the real estate sector. As for the basic sector, namely the specific provision of generated electricity and gas; water supply, waste management, waste, and recycling; construction; wholesale and retail trade; car and motorcycle repair; transportation and warehousing; providing accommodation and food and drink; information and communication; financial and insurance services; real estate; local government administration, civil defense, and compulsory social security; education services; preventive health services and social activities; other services. non-basic sectors, namely agriculture, divinity, and local fisheries; extensive mining and extensive excavation; processing industry and corporate services.